Peritubular Capillary Basement Membrane Multilayering in Renal Allograft Biopsies of Patients With De Novo Donor-Specific Antibodies. Issue 4 (April 2016) - de Kort, Hanneke; Willicombe, Michelle; Brookes, Paul; Moran, Linda B; Santos-Nunez, Eva; Galliford, Jack W.; Taube, David; McLean, Adam G.; Moss, Jill; Cook, H. Terence; Roufosse, Candice
Abstract : Background: Severe peritubular capillary basement membrane multilayering (PTCBML) is part of the Banff definition of chronic antibody-mediated rejection. We retrospectively investigated whether assessment of the mean number of layers of basement membrane (BM) around peritubular capillaries (PTC) can be used in a cohort of patients with de novo donor-specific antibodies (dnDSA) as an early marker to predict long-term antibody-mediated injury. Methods: This is a retrospective cohort study with 151 electron microscopy samples from 54 patients with dnDSA, assessed at around 1 year after transplantation, for a mean number of BM layers around PTC and in serial biopsies. Graft survival and time to transplant glomerulopathy (TG) development were estimated in survival analyses. Results: We found that a mean PTCBML count greater than 2.5 layers assessed in a sample of 25 PTCs around 1 year after transplantation is indicative of the development of TG in patients with dnDSA ( P = 0.001). In addition, in patients with serial biopsies available for electron microscopy analysis, we could distinguish 2 groups: patients with a mean PTCBML count of 2.5 or less on all biopsies, and patients who developed greater than 2.5 layers at any time after transplantation. The latter group reflected dnDSA patients at risk for TG development ( P < 0.001). In patients with dnDSA, PTCBML score added significantly to the sensitivity and specificity of prediction of TG compared with microcirculation injury score alone. Conclusions: Our results highlight the potential value of assessing the mean number of BM in PTC for early prediction of progression to chronic antibody-mediated injury. Abstract : Peritubular capillary basement membrane multilayering with a mean count of >2.5 layers can be a good early marker to predict long-term antibody-mediated injury in a cohort of kidney transplant recipients with de novo donor-specific antibodies.